1998
DOI: 10.1067/msy.1998.91182
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal reperfusion-induced pulmonary edema is related to increased pulmonary inducible nitric oxide synthase activity

Abstract: These data are consistent with the hypothesis that the release of nanomolar quantities of nitric oxide generated by iNOS contributes to IR-induced pulmonary microvascular dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…Constitutive NOS is protective in IRI, whereas inducible NOS is responsible for lung dysfunction [34]. Turnage et al [37,38] demonstrated the deleterious role of inducible NOS in the lung after intestinal IRI. Matsuyama et al [39] and Kosaka et al [40] reported that COX-2 and iNOS are up-regulated and have deleterious effects on renal IRI, which is in agreement with the present results.…”
Section: Discussionmentioning
confidence: 99%
“…Constitutive NOS is protective in IRI, whereas inducible NOS is responsible for lung dysfunction [34]. Turnage et al [37,38] demonstrated the deleterious role of inducible NOS in the lung after intestinal IRI. Matsuyama et al [39] and Kosaka et al [40] reported that COX-2 and iNOS are up-regulated and have deleterious effects on renal IRI, which is in agreement with the present results.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous clinical studies have clarified that perioperative hypovolemia, hemodynamic instability, and/or low cardiac output syndrome predicts morbidity and mortality following CPB 71,72 . Experimental splanchnic ischemia–reperfusion has been shown to induce lung recruitment and sequestration of neutrophils, 73 free radical injury, and increased pulmonary iNOS expression, while cytokines, and in particular TNF‐α, seem to play a central role to this process 74 . In addition, translocation of toxins and microbial flora may occur following intestinal ischemia leading to ischemic compromise of the integrity of the mucosal barrier 75 …”
Section: Pathophysiology Of Lung Dysfunction Following Open Heart Surmentioning
confidence: 99%
“…The resulting splanchnic ischemia and subsequent reperfusion can lead to both local intestinal and remote organ injury [1, 2, 3]. The mechanisms underlying the pathological changes in nonischemic organs are very complex and to date not fully understood, though evidence for the involvement of a number of inflammatory mediators is emerging, such as cytokines, arachidonic acid products, phagocytic cells, reactive oxygen species and also it seems that NO generated by inducible nitric oxide (iNOS) is involved [2, 4, 5, 6, 7, 8]. It has been shown in clinical studies as well as in animal models that intestinal ischemia-reperfusion (I/R) may lead to damage to the pulmonary function [2, 3, 4].…”
Section: Introductionmentioning
confidence: 99%